EULAR recommendations for the management of systemic lupus erythematosus. Report of a Task Force of the EULAR Standing Committee for International Clinical Studies Including Therapeutics. Issue 2 (15th May 2007) - Bertsias, G; Ioannidis, J P A; Boletis, J; Bombardieri, S; Cervera, R; Dostal, C; Font, J; Gilboe, I M; Houssiau, F; Huizinga, T; Isenberg, D; Kallenberg, C G M; et al.
Abstract : Objective: Systemic lupus erythematosus (SLE) is a complex disease with variable presentations, course and prognosis. We sought to develop evidence-based recommendations addressing the major issues in the management of SLE. Methods: The EULAR Task Force on SLE comprised 19 specialists and a clinical epidemiologist. Key questions for the management of SLE were compiled using the Delphi technique. A systematic search of PubMed and Cochrane Library Reports was performed using McMaster/Hedges clinical queries' strategies for questions related to the diagnosis, prognosis, monitoring and treatment of SLE. For neuropsychiatric, pregnancy and antiphospholipid syndrome questions, the search was conducted using an array of relevant terms. Evidence was categorised based on sample size and type of design, and the categories of available evidence were identified for each recommendation. The strength of recommendation was assessed based on the category of available evidence, and agreement on the statements was measured across the 19 specialists. Results: Twelve questions were generated regarding the prognosis, diagnosis, monitoring and treatment of SLE, including neuropsychiatric SLE, pregnancy, the antiphospholipid syndrome and lupus nephritis. The evidence to support each proposition was evaluated and scored. After discussion and votes, the final recommendations were presented using brief statements. The average agreement among experts was 8.8 out of 10. Conclusion: Recommendations for the management of SLE were developed using an evidence-based approach followed by expert consensus with high level of agreement among the experts.